2000
DOI: 10.1128/cdli.7.5.856-857.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Dengue Antibodies against Structural and Nonstructural Proteins

Abstract: Antibodies against dengue virus type 2 and 4 proteins in acute-phase sera of 10 primary and 10 secondary dengue fever and dengue hemorrhagic fever patients were studied by Western blotting. In the first group the immune response was barely detectable, while in the second group more proteins were detected, with a very strong reaction. Anti-NS1 and -NS3 antibodies were detected mainly in secondary cases. Anti-E, -NS3, and -NS5 antibodies were detected in a high number of cases. The possibility of implementing ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 6 publications
5
74
2
Order By: Relevance
“…In addition, heat denaturation of the protein significantly reduced the reaction of the protein with the tested human sera, which indicates that the recombinant protein maintains structural features of the native viral protein. Recognition of NS5 by antibodies from DENVinfected patients has been reported previously (59). Nonetheless, our results demonstrated that antibodies in DENV-infected subjects recognized both linear and conformational epitopes of the protein.…”
Section: Discussioncontrasting
confidence: 37%
“…In addition, heat denaturation of the protein significantly reduced the reaction of the protein with the tested human sera, which indicates that the recombinant protein maintains structural features of the native viral protein. Recognition of NS5 by antibodies from DENVinfected patients has been reported previously (59). Nonetheless, our results demonstrated that antibodies in DENV-infected subjects recognized both linear and conformational epitopes of the protein.…”
Section: Discussioncontrasting
confidence: 37%
“…The possibility of anti-NS1 antibodies resulting from a previous infection in quenching the NS1 antigen of a current infection has been discussed to explain this observation (Valdes et al 2000, Libraty et al 2002, Koraka et al 2003. Nevertheless, NS1 assay was found to have around 50% sensitivity among secondary dengue infections in Singapore, where approximately 45% of dengue cases are secondary infections (Low et al 2006).…”
Section: Ns1 Antigen Assays For Dengue Diagnostics and Surveillancementioning
confidence: 99%
“…Recent studies indicate that anti-NS1 and -NS3 antibodies are detected mainly in secondary infections while those anti-E and anti-NS3 antibodies are detected in both primary and secondary infections (Valdés et al 2000). This fact indicates that virus proteins derived from strains of the viruses that are causing disease in a given area are more useful for dengue virus diagnostic in that endemic area.…”
mentioning
confidence: 95%